Phytoplasma diseases of grapevine and the possible measures to control them - Kölber, M. (International Journal of Horticultural Science, 2011)
Phytoplasmas are a special group of phloem-living pathogens in several plant species. Grapevine yellows (GY) is a term for phytoplasma diseases occurring on Vitis vinifera and inducing the same or very similar symptoms and causing severe losses worldwide. Flavescence Dorée (16SrV) phytoplasma (FD, species name: ‘Candidatus Phytoplasma vitis’) is considered a quarantine pest in several countries due to its epidemic character and high economic loss it provokes. The leafhopper Scaphoideus titanus is the univoltine and monophagous vector of FD. Bois noir disease caused by stolbur (16SrXII-A) phytoplasma (species name: ‘Candidatus Phytoplasma solani’) is described under different disease names in different countries. Hyalesthes obsoletus (Cixiidae) is the only proved polyphagous vector of BN. However, distribution of BN disease is increasing also on those areas where H. obsoletus is not prevalent or only in a very low number. Therefore the presence of other vectors cannot be concluded. The ‘Tuf-a’ type Stolbur phytoplasma is associated with stinging nettle (Urtica dioica) and the tuf-b type one to field bindweed (Convolvulus arvensis). There are only preventive control measures against phytoplasmas: the use of pathogen-free propagating material, hot water treatment of propagating material, as well as control of vectors and weeds. S. titanus can be efficiently controlled by insecticide treatments. However, in case of H. obsoletus, insecticides are not effective due to the biological characters and feeding habits of the vector.Weed control can reduce H. obsoletus specimen and their abundance to a certain extent. Extensive research is needed on wild hosts of GY phytoplasmas especially on BN phytoplasma and its vectors to the better understanding of their epidemiology.